2018
DOI: 10.1089/dna.2017.4081
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect of Cadmium, Lead, and Arsenic on the Sertoli Cell: Mechanisms of Damage Involved

Abstract: Over the past decades, an increase has been described in exposure to environmental toxins; consequently, a series of studies has been carried out with the aim of identifying problems associated with health. One of the main risk factors is exposure to heavy metals. The adverse effects that these compounds exert on health are quite complex and difficult to elucidate, in that they act at different levels and there are various signaling pathways that are implicated in the mechanisms of damage. The Sertoli cells pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 80 publications
1
22
0
2
Order By: Relevance
“…A study has shown that synergism between lead, cadmium, and mercury can cause damage to kidney function [42]. Lead also targets testicular Sertoli cells, which may affect sperm production [43]. Lead toxicity in a children's nervous system will cause typical neurological symptoms [44].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that synergism between lead, cadmium, and mercury can cause damage to kidney function [42]. Lead also targets testicular Sertoli cells, which may affect sperm production [43]. Lead toxicity in a children's nervous system will cause typical neurological symptoms [44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cd 2+ is potentially carcinogenic and teratogenic, causing several abnormalities [24,25]. Cd 2+ also contributes to the genotoxicity of other agents that may cause damage to the DNA structure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of industrialization, owing to the bioaccumulation potential, harmful effects, pervasiveness, and persistence in the environment; heavy metals‐induced toxicity have become one of the main health concerns. [ 8,9 ]…”
Section: Introductionmentioning
confidence: 99%